2017
DOI: 10.1093/nar/gkx468
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated SIRT1 associates with replication origins to prevent excess replication initiation and preserve genomic stability

Abstract: Chromatin structure affects DNA replication patterns, but the role of specific chromatin modifiers in regulating the replication process is yet unclear. We report that phosphorylation of the human SIRT1 deacetylase on Threonine 530 (T530-pSIRT1) modulates DNA synthesis. T530-pSIRT1 associates with replication origins and inhibits replication from a group of ‘dormant’ potential replication origins, which initiate replication only when cells are subject to replication stress. Although both active and dormant ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 72 publications
1
51
1
Order By: Relevance
“…As shown in Fig. 6c, density plots comparing replication origin utilization in SIRT1 proficient and deficient samples clearly demonstrate that the SIRT1-deficient sample exhibited a higher level of replication origin utilization as reported 8 . In contrast, the MLN4924treated samples did not exhibit a similar bias ( Fig.…”
Section: Genomic Distribution Of Re-replicated Dnasupporting
confidence: 70%
See 3 more Smart Citations
“…As shown in Fig. 6c, density plots comparing replication origin utilization in SIRT1 proficient and deficient samples clearly demonstrate that the SIRT1-deficient sample exhibited a higher level of replication origin utilization as reported 8 . In contrast, the MLN4924treated samples did not exhibit a similar bias ( Fig.…”
Section: Genomic Distribution Of Re-replicated Dnasupporting
confidence: 70%
“…On each chromosome, replication starts at distinct regions termed replication origins, which initiate replication sequentially during S phase. DNA synthesis initiates at replication origins once the helicases incorporated into pre-replication complexes are activated, forming active replication forks 4,7,8 . As the helicases are activated, the pre-replication complex proteins responsible for recruiting helicases to chromatin are degraded, preventing the further recruitment of helicases to the genomic regions already undergoing duplication 9-12 . In metazoans, pre-replication complexes are bound to chromatin in excess, but chromosome duplication initiates only at a fraction of the many potential origins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Studies have demonstrated that some histone deacetylase inhibitors can eliminate quiescent leukemic stem cells and reduce drug resistance in CML. [10][11][12][13] Sirtuin 1 (SIRT1), a member of the sirtuin family modulates several processes such as DNA repairing, cell cycle, metabolism, aging, and cell survival under stress conditions. [10][11][12][13] Sirtuin 1 (SIRT1), a member of the sirtuin family modulates several processes such as DNA repairing, cell cycle, metabolism, aging, and cell survival under stress conditions.…”
mentioning
confidence: 99%